FORMULASI DAN EVALUASI STABILITAS FISIK SERUM WAJAH EKSTRAK MINYAK BIJI ANGGUR (Vitis vinifera L) - Zulfa Aqillah; Nia Yuniarsih; Dadan Ridwanullah (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2022)
Skin care is needed so that the skin is not dry, rough and dull, one of the cosmetics to overcome skin aging that contains antioxidants is grape seed oil which has a high vitamin E content and is beneficial for skin health. Serum is a preparation with a high concentration of active ingredients and low viscosity that delivers a thin film of the active ingredient on the skin surface. The purpose of this study was to formulate grape seed oil extract (Vitis vinifera) in serum to determine the physical stability stored in three different conditions, namely room temperature 27°C, high temperature 40°C and under sunlight. The method used in this study is experimental laboratory and accelerated stability testing. The results of this study made three formulas in various concentrations of grape seed oil extract, namely 4%, 6%, 8%. The stability of the preparation can be seen based on the results of organoleptic testing, pH, viscosity, and homogeneity. The results of the physical stability test of serum preparations were processed using statistics using the One Way ANOVA method. The conclusion of this study is that grape seed oil extract can be made into facial serum preparations, and the results of this study indicate that the three formulas are more stable at room temperature storage of 27°C, high temperature of 40°C and under sunlight.